Development and optimization of a sensitive TaqMan® real‐time PCR with synthetic homologous extrinsic control for quantitation of Human cytomegalovirus viral load. Issue 9 (8th March 2016) - Slavov, Svetoslav Nanev; Otaguiri, Katia Kaori; de Figueiredo, Glauciane Garcia; Yamamoto, Aparecida Yulie; Mussi‐Pinhata, Marisa Marcia; Kashima, Simone; Covas, Dimas Tadeu
Abstract : Human cytomegalovirus ( Human herpesvirus 5, HCMV) causes frequent asymptomatic infections in the general population. However, in immunosuppressed patients or congenitally infected infants, HCMV is related to high morbidity and mortality. In such cases, a rapid viral detection is crucial for monitoring the clinical outcome and the antiviral treatment. In this study, we optimized a sensitive biplex TaqMan® real‐time PCR for the simultaneous detection and differentiation of a partial HCMV UL97 sequence and homologous extrinsic control (HEC) in the same tube. HEC was represented by a plasmid containing a modified HCMV sequence retaining the original primer binding sites, while the probe sequence was substituted by a phylogenetically divergent one (chloroplast CF0 subunit plant gene). It was estimated that the optimal HEC concentration, which did not influence the HCMV amplification is 1, 000 copies/reaction. The optimized TaqMan® PCR demonstrated high analytical sensitivity (6.97 copies/reaction, CI = 95%) and specificity (100%). Moreover, the reaction showed adequate precision (repeatability, CV = 0.03; reproducibility, CV = 0.0027) and robustness (no carry‐over or cross‐contamination). The diagnostic sensitivity (100%) and specificity (97.8%) were adequate for the clinical application of the molecular platform. The optimized TaqMan® real‐time PCR is suitable for HCMV detection and quantitation in predisposed patients and monitoring of the applied antiviral therapy. J. Med. Virol. 88:1604–1612, 2016 . © 2016 Wiley Periodicals, Inc.